2007
DOI: 10.1073/pnas.0705285104
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 and Akt2 are required for αβ thymocyte survival and differentiation

Abstract: The ␤-selection checkpoint in ␣␤T lymphocyte development occurs at the double negative (DN) 3 (CD4 ؊ CD8 ؊ CD25 ؉ c-kit ؊ ) stage, when further differentiation requires a signal from the newly rearranged TCR ␤ chain. Thymocytes with mutations in key signaling molecules in the phosphatidylinositol 3-kinase-Akt pathway manifest defects in survival, proliferation, and differentiation past the ␤-selection checkpoint. However, little information is available regarding the role of Akt itself in thymocyte development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(162 citation statements)
references
References 39 publications
(44 reference statements)
11
143
3
Order By: Relevance
“…4 ). Consistent with our results, it has been reported that combined loss of Akt1/2 causes increased apoptosis after stimulation in thymocytes ( 20 ). Inhibition of Akt signaling induces apoptosis in 3T3-L1 adipocytes ( 48 ).…”
Section: Both Akt1 and Akt2 Mediate Insulin-induced Downregulation Ofsupporting
confidence: 82%
“…4 ). Consistent with our results, it has been reported that combined loss of Akt1/2 causes increased apoptosis after stimulation in thymocytes ( 20 ). Inhibition of Akt signaling induces apoptosis in 3T3-L1 adipocytes ( 48 ).…”
Section: Both Akt1 and Akt2 Mediate Insulin-induced Downregulation Ofsupporting
confidence: 82%
“…This result correlates with the increased susceptibility of CD4 1 Foxp3 À CD5 À/À thymocytes to apoptosis. In this context, Akt was shown to play a role in thymocyte survival [63,64], through the induction of Bcl-2 family members, such as Bcl-XL [65] and A1 [66].…”
Section: Discussionmentioning
confidence: 99%
“…This result correlates with the increased susceptibility of CD4 1 Foxp3 À CD5 À/À thymocytes to apoptosis. In this context, Akt was shown to play a role in thymocyte survival [63,64], through the induction of Bcl-2 family members, such as Bcl-XL [65] and A1 [66].In contrast to naïve thymocytes, the absence of CD5 did not affect Akt phosphorylation in Treg, in response to TCR crosslinking. Interestingly, Bensinger et al [67] recently showed that peripheral Treg, stimulated in the presence of IL-2, show increased survival in the absence of Akt phosphorylation, suggesting that Akt activation is dispensable for Treg survival.…”
mentioning
confidence: 99%
“…6,10,11 These joined signals activate the PI3K/AKT/mTOR-pathway that has been shown to play a pivotal role in regulating CD8 + T cell differentiation and memory formation. 12,13 Interestingly however, interference of PI3K/AKT signaling does not severely impair the proliferation of murine CD8 + T cells. 14 Therefore, we and others exploited pharmacological AKT-inhibition to generate early memory T SCM/CM -like CD8 + T cells for ex vivo adoptive cell therapy.…”
Section: Introductionmentioning
confidence: 99%